The challenges of implementing modular, adaptive, and decentralised water technologies – the perspective of a rural service provider in Kenya - Nyaga, C; Katuva, J; Thomson, P (Elsevier, 2024)
FundiFix is a social enterprise that offers rural water systems maintenance service in rural Kenya. In recent years FundiFix has been operating these three types of water system that fall under the MAD (modular, adaptive, and decentralised) water systems paradigm: Solar powered groundwater kiosks, water ATMs, and reverse osmosis filtrations systems. This article outlines some of the challenges of operating these in a rural context. We identify four key challenges that must be considered if these technologies are to provide sustainable benefits to rural communities: managing higher capital and maintenance costs; the requirement for more skilled staff to manage and maintain them; the risk of the most marginalised communities being left behind; the importance of considering maintenance from the start.